Clonal Hypereosinophilic Syndrome: Two Cases Report in Black Men from Sub-Saharan Africa and Literature Reviews. (27th February 2011) - Messie Messie, Kodjovi Kodjovi; Vovor Vovor, Ahoefa Ahoefa; Kueviakoe Kueviakoe, Irenee Messanh Irenee Messanh; Sallah Sallah, Levi kankoe Levi kankoe; Agbetiafa Agbetiafa, Kossi Kossi; Segbena Segbena, Akuete Yvon Akuete Yvon
Abstract : The first case is about a man of 60 years old suffering of hypereosinophilic syndrome (HES) developed since 1998. He presented chronic cough, insomnia, and negative parasitical test. We observed hypereosinophilia and fibroblastic hyperplasia at the bone marrow biopsy. Initially, hydroxyurea and α -interferon treatment failed. We proposed to him imatinib mesylate in May 2003. The FIP1L1-PDGFRA gene was detected. The second case is about a man of 34 years old seen in March 2002. First investigation concluded to CML. Progressively, eosinophil cells increased, and complications occurred as oedema syndrome, dyspnoea, and parietal chronic endocarditic fibrosis associated with pericarditis. In addition, a bowel obstruction happened and was cured by surgery. Bcr-abl fusion was negative, and FIP1L1-PDGFRA gene was detected after and imatinib mesylate was given. Actually, endocarditic fibrosis decreased. The two patients are in haematological and cytogenetic remission. We concluded that clonal HES is present in Africa, and imatinib mesylate is effective.